Profil Pertumbuhan Mikroorganisme pada Fermentasi Biji Kakao Aceh - Murna Muzaifa; Yusya Abubakar; Faitzal Haris (Agricultural Faculty, 2017)
Fermentation process is the most crucial step in the formation of the flavor and aroma of the cocoa bean. Cocoa bean fermentation triggers an array of chemical changes within the bean.These chemical changes are vital to the development of the complex and much-loved flavour known as “chocolate”. Fermentation involves a number of specific microorganisms that play a role during fermentation. The aim of this research was to analized microorganism growth profil of Aceh cacao during fermentation. Fermentation was conducted on 6 days with different aerations (agitation every 24 and 48 hours). The result showed that growth profile of microorganism during fermentation relatively had similar trend. Yeast dominated on the early fermentation, lactid bacteria reached the higest population on day 3 and acetic acid bacteria on day 4. Better quality of fermented cacao was resulted on every 48 hours of agitation that reached 70,19% of full fermentation.